The miR-130a-3p/TGF-βRII Axis Participates in Inhibiting the Differentiation of Fibroblasts Induced by TGF-β1 - Yanhong Liu; Yan Ding; Yapeng Hou; Tong Yu; Hongguang Nie; Yong Cui (Frontiers Media S.A., 2021)
Pulmonary fibrosis (PF) is a chronic progressive interstitial lung disease that has a poor prognosis. Abnormal activation of transforming growth factor-β1 (TGF-β1) plays a crucial role in fibroblast differentiation. Mesenchymal stem cells (MSCs) are currently being considered for the treatment of PF, but the regulatory mechanisms are poorly understood. We co-cultured bone marrow-derived MSCs and mouse lung fibroblasts (MLg) in the presence of TGF-β1, and studied the protein/mRNA expression of fibrosis markers and related signaling pathways. The effects of miR-130a-3p and TGF-β receptor II (TGF-βRII) on the differentiation of MLg induced by TGF-β1 were studied using immunofluorescence assay, Western blot, and quantitative real-time PCR techniques, respectively. Our results showed that MSCs reversed the overexpression of fibrosis markers and TGF-β1/Smad signaling pathway proteins and mRNAs after TGF-β1 treatment and increased the level of miR-130a-3p. TGF-βRII was identified as a target of miR-130a-3p and was evaluated by dual-luciferase reporter assay. The miR-130a-3p/TGF-βRII axis could suppress the differentiation of lung fibroblasts via the TGF-β1/Smad signaling pathway, thereby reducing the process of PF.